1970
DOI: 10.3329/bjpt.v17i1.5386
|View full text |Cite
|
Sign up to set email alerts
|

The micromorphological and anatomical properties of <i>Onosma angustissimum</i> Hausskn. & Bornm. and <i>O. cassium</i> Boiss. (Boraginaceae)

Abstract: The micromorphological and anatomical properties of Onosma angustissimum Hausskn. & Bornm. and O. cassium Boiss. were investigated. O. angustissimum is an endemic species. All examined taxa had secondary root structure. Crystals were seen in the stem and leaves of two species. Epidermal cells containing crystal needles were observed in O. cassium. Studied Onosma species had isobilateral type of leaves. Stomata were anisocytic and anomocytic. Glandular and eglandular trichomes especially porrectstellate and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
6
9
0
Order By: Relevance
“…The setae surface of those species cover dense or sparse papilae, where setae of O. stenoloba consist of tubercles with pilies at the base. The findings based on anatomical and micromorphological studies were found somewhat consistent with those of Akçin and Engin (2001), and Akçin and Binzet (2010). However, our results differs from those earlier studies in terms of number of layers of cells and tissues, the density of trichomes and the types of leaf mesophyll (Fig.…”
Section: Micromorphological Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…The setae surface of those species cover dense or sparse papilae, where setae of O. stenoloba consist of tubercles with pilies at the base. The findings based on anatomical and micromorphological studies were found somewhat consistent with those of Akçin and Engin (2001), and Akçin and Binzet (2010). However, our results differs from those earlier studies in terms of number of layers of cells and tissues, the density of trichomes and the types of leaf mesophyll (Fig.…”
Section: Micromorphological Studiessupporting
confidence: 92%
“…Metcalfe and Chalk (1950) studied the anatomy of the family Boraginaceae and found setae (hairs), epidermal surface and cystoliths as diagnostic characters. Several attempts have been made on micromorphology and anatomy of different Turkish species of Onosma Engin, 2001, 2005;Akçin, 2004Akçin, , 2007Binzet and Akçin, 2009;Akçin and Binzet, 2010). Micromorphological studies of epidermal and nutlet surface of some Onosma taxa highlighted the importance of these features (Akçin, 2009;Binzet and Akçin, 2009;Akçin et al, 2013;Mehrabian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Trend from heterogenous to homogenous has been noted as a reliable tool to infer specialization; a primitive position for heterogenous rays and an advanced position for homogenous wood rays have been suggested (Outer and Veenandal, 1997;Folorunso and Awosika, 2013 The study of the leaf epidermal surfaces of Ludwigia revealed a number of important micromorphological characters and these characters exhibit interesting variations that are of significance for identification. These findings support previous studies in some other genera where leaf and stem anatomical characters have been used as a veritable taxonomic tool (Adedeji and Illoh, 2004;Saheed and Illoh, 2010;Akçin and Binzet, 2010;Folorunso and Awosode, 2013).…”
supporting
confidence: 91%
“…Although the polytomies obtained in Weigend et al Anatomical and morphological characters to indicate phylogenetic relationships among taxa (Metcalfe & Chalk, 1979). Also, it is well known that anatomical traits provide taxonomically significant data in the numerous angiosperms including Boraginaceae family (Akçin & Binzet, 2010;Beyazo glu, Türkmen, Coşkunçelebi, Makbul, & Kodal, 2008;Binzet & Akçin, 2012;Coşkunçelebi, Makbul, Türkmen, & Beyazo glu, 2008;Makbul, Türkmen, Kandemir, & Beyazoglu, 2008). Metcalfe and Chalk (1979) pointed out that family Boraginaceae has both bifacial and isobilateral leaves.…”
Section: Discussionmentioning
confidence: 99%